Pengaruh Kualitas Produk, Kualitas Pelayanan, Dan Harga Terhadap Keputusan Pembelian Pada Kebab Wathanku Di Pondok Gede Bekasi - Angel Maharani; Widi Winarso; Kardinah Indrianna Meutia; Milda Handayani; Rini Wijayaningsih (Jurnal Penelitian Ekonomi Manajemen dan Bisnis, 2024)
This study aims to evaluate the impact of product quality, service quality, and price on kebab purchasing decisions at Wathanku restaurants. Kebabs have become one of the popular culinary and in wide demand by the public. Factors such as product quality, service quality, and price are believed to have a significant role in shaping consumer purchasing decisions. This research is a quantitative research using purposive sampling method. The source of this research data is primary data in the form of questionnaires or questionnaires that have been distributed to 112 respondents. Data processing using SPSS (Statistical Package for the Social Sciences) analysis technique. Research findings show that product quality, service quality, and price together have a positive and significant influence on kebab purchasing decisions in Wathanku. Superior product quality provides a positive experience to consumers, while satisfactory service quality increases customer confidence. Competitive pricing factors are also an important aspect in shaping consumer purchasing decisions.